Kinematics and kinetics during stair ascent in individuals with Gluteal Tendinopathy. (December 2016) - Allison, Kim; Vicenzino, Bill; Bennell, Kim L; Wrigley, Tim V; Grimaldi, Alison; Hodges, Paul W.
Abstract: Background: Individuals with gluteal tendinopathy commonly report lateral hip pain and disability during stair ascent. This study aimed to compare kinematics and kinetics between individuals with and without gluteal tendinopathy during a step up task. Methods: 35 individuals with unilateral gluteal tendinopathy and 35 pain-free controls underwent three-dimensional motion analysis of stance phase during stair ascent. An analysis of covariance was performed to compare hip, pelvis and trunk kinematic and kinetic variables between groups. A K-means cluster analysis was performed to identify subgroups from the entire group ( n  = 70) based on the characteristics of the external hip adduction moment. Finally, a Newcombe-Wilson test was performed to evaluate the relationship between group and cluster codes and a 3 × 2 ANOVA to investigate the differences in kinematics between groups and cluster codes. Findings: Individuals with gluteal tendinopathy exhibited a greater hip adduction moment impulse during stair ascent (ES = 0.83), greater internal rotation impulse during the first 50% stance phase (ES = 0.63) and greater contralateral trunk lean throughout stance than controls (ranging from ES = 0.67–0.93). Three subgroups based on hip adduction moment characteristics were identified. Individuals with GT were 4.5 times more likely to have a hip adduction moment characteristic of a large impulse and greater lateral pelvic translation at heel strike than the subgroup most likely to contain controls. Interpretation: Individuals with GT exhibit greater hip adduction moment impulse and alterations in trunk and pelvic kinematics during stair ascent. Findings provide a basis to consider frontal plane trunk and pelvic control in the management of gluteal tendinopathy. Highlights: Hip adduction moment is larger during step up in those with gluteal tendinopathy Contralateral trunk lean in step up is greater in those with gluteal tendinopathy Lateral shift of the pelvis is associated with gluteal tendinopathy in step up Addressing step up biomechanics may be relevant for gluteal tendinopathy management